Pelatihan Pembuatan dan Pemasaran Media Promosi Digital untuk Destinasi River Tubing Lokal di Desa Sama Guna - Khaerul Anam; Kukuh Tri Admaja; Lilik Evitamala; Hasbi Hasbi; Yadi Imansyah (Jurnal Informasi Pengabdian Masyarakat, 2024)
This community service activity aims to address the issue of inadequate promotion of the river tubing tourist destination in Sama Guna Village, which has led to a low number of tourist visits. The lack of effective promotion has prevented this natural tourism potential from optimally contributing to the local community's economy. To tackle this issue, the study aims to design and market digital promotional media capable of reaching a broader target market. The methods used in this activity include the design phase of digital promotional media, training for the local community on the use of digital technology, and the implementation of digital marketing strategies through social media platforms and websites. A participatory approach was employed to involve the community in each stage of the activity, ensuring knowledge transfer and program sustainability. The results of this community service activity showed a significant 75% increase in tourist visits to the river tubing destination in Sama Guna Village following the implementation of digital promotion, compared to the previous rate of only 50%. Additionally, the local community experienced an improvement in their skills in using digital technology to promote their products and services, which ultimately contributed to increased income and economic well-being in the village.